Abnormal premotor–motor interaction in heterozygous Parkin- and Pink1 mutation carriers. Issue 1 (January 2017) - Weissbach, Anne; Bäumer, Tobias; Pramstaller, Peter P.; Brüggemann, Norbert; Tadic, Vera; Chen, Robert; Klein, Christine; Münchau, Alexander
Highlights: Asymptomatic heterozygous Parkin/PINK1 mutation carriers show altered premotor–motor inhibition. A singlel -dopa administration could partly reverse this alteration. These mutation carriers can serve as in vivo models to study pre-symptomatic stages of Parkinsonism. Abstract: Objectives: Mutations in the Parkin and PINK1 gene account for the majority of autosomal recessive early-onset Parkinson cases. There is increasing evidence that clinically asymptomatic subjects with single heterozygous mutations have a latent nigrostriatal dopaminergic deficit and could be taken as in vivo model of pre-symptomatic phase of Parkinsonism. Methods: We charted premotor–motor excitability changes as compensatory mechanisms for subcortical dopamine depletions using transcranial magnetic stimulation by applying magnetic resonance-navigated premotor–motor cortex conditioning in 15 asymptomatic, heterozygous Parkin and PINK1 mutation carriers (2 female; mean age 53 ± 8 years) and 16 age- and sex-matched controls (5 female; mean age 57 ± 9 years). Participants were examined at baseline and after acutel -dopa challenge. Results: There werel -dopa and group specific effects during premotor–motor conditioning at an interstimulus interval of 6 ms indicating a normalisation of premotor–motor interactions in heterozygous Parkin and PINK1 mutation carriers afterl -dopa intake. Non-physiologically high conditioned MEP amplitudes at this interval in mutation carriers decreased afterl -dopa intake but increased in controls. Conclusion: Premotor–motor excitability changes are part of the cortical reorganization in asymptomatic heterozygous Parkin - and PINK1 mutation carriers. Significance: These subjects offer opportunities to delineate motor network adaptation in pre-symptomatic Parkinsonism.